La responsabilidad social corporativa en la gestión administrativa de la cooperativa de Ahorro y Crédito COACMES - Salvatierra Zambrano, Jennifer Estephanía (2024)
The objective of this research project is to structure a management system in Corporate Social Responsibility for the administrative management of COACMES, for an adequate application of policies oriented to the sustainability of the organization focused on its three axes (economic, social and environmental). The approach methodology was descriptive due to its usefulness in interpreting demographic data of the population under study, as well as field data, due to its approach to the target audience. An interview and survey that went through a validation process were used. To obtain and achieve the results, four methodological phases were structured that allowed the outcome of each of the research activities, in the first phase, a diagnosis of corporate social responsibility was made in the administrative management of COACMES, the which was achieved through a documentary review of strategic planning and through an interview directed to the managers, the second phase consisted of establishing the correlation of the variables under study through the results obtained in the survey itself that was directed to the collaborators, partners and the community, and finally in the third phase the management system based on the Iso 26000 Standard was structured as a contribution to the administrative management processes. It is concluded that Social Responsibility must be immersed in each of the administrative management processes so that the activities carried out are clearly sustainable and sustainable.